Specific inhibition of DNMT1/CFP1 reduces cancer phenotypes and enhances chemotherapy effectiveness. (June 2014) - Cheray, Mathilde; Nadaradjane, Arulraj; Bonnet, Pascal; Routier, Sylvain; Vallette, François M; Cartron, Pierre-François
Aim: DNA methylation is a fundamental biologic process of genomes and is a candidate for pharmacological manipulation that might have important therapeutic advantages. Thus, DNA methyltransferases (DNMTs) appear to be ideal targets for drug intervention.Materials & methods: To develop a new generation of DNMT inhibitor, we analyzed the ability of peptides to selectively inhibit certain DNMT1-incuding complexes.Results: Our study demonstrates that the disruption of DNMT1/CFP1-including complexes increases the efficiency of chemotherapeutic treatment on established tumors in mice.Conclusion: Our data opens a promising and innovative alternative to the development of DNMT inhibitors.